Effect of different burning degrees of sugarcane leaf ash on the properties of ultrahigh-strength concrete - Agwa, Ibrahim Saad; Zeyad, Abdullah M.; Tayeh, Bassam A.; Amin, Mohamed (Journal of Building Engineering, 2022)
The global expansion of agricultural production increases agricultural waste ash (AWA). Accordingly, AWA should be disposed to preserve the environment. This study focuses on using AWA as a partial substitute for cement to produce ultrahigh-strength concrete (UHSC). This research investigated the effect of using sugarcane leaf ash (SLA) as a pozzolanic material on the properties of UHSC. The cement replacement rates by SLA were 10%, 20% and 30% by weight. SLA was heat-treated at 400, 500, 600, 700 and 800 °C for 2 h to improve its physical and chemical properties. The effects of the heat-treated SLA on UHSC mechanical properties such as, compressive strength, split tensile strength, flexural strength and modulus of elasticity, were studied. The effects of heat-treated SLA on UHSC durability such as, water permeability, chloride penetration and sorptivity of UHSC were also investigated. In addition to, microstructure analysis of several UHSC mixtures was presented. Results showed the efficiency of SLA as a partial substitute of the 20% of cement weight with mechanical properties and durability higher than the mechanical properties and durability of the reference mixture. Compared with the reference mixture, the heat-treated SLA used as a partial substitute generally improved all properties. The UHSC containing SLA heat-treated at 700 °C and a 20% substitution rate achieved the best results of 162.5, 17.78, 24.05 and 55,820 MPa for compressive strength, tensile strength, bending strength and modulus of elasticity at test age of 28 days. •SLA is a new material that among the list of cementitious materials, contains SiO2 by 83.30% of its mass at heat-treated 700 °C.•Replacement of cement up to 20% of (SLA) heat-treated at 700 °C significantly enhances the mechanical properties of concrete.•UHSC up to 162.5MPa can be produced by replacement of cement up to 20% of sugarcane leaf ash (SLA).